2018
DOI: 10.1021/acsomega.7b02096
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent ZnO–Au Nanocomposite as a Probe for Elucidating Specificity in DNA Interaction

Abstract: In this work, we report the interaction of a fluorescent ZnO–Au nanocomposite with deoxyribonucleic acid (DNA), leading to AT-specific DNA interaction, which is hitherto not known. For this study, three natural double-stranded (ds) DNAs having different AT:GC compositions were chosen and a ZnO–Au nanocomposite has been synthesized by anchoring a glutathione-protected gold nanocluster on the surface of egg-shell-membrane (ESM)-based ZnO nanoparticles. The ESM-based bare ZnO nanoparticles did not show any select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 88 publications
(166 reference statements)
3
17
0
Order By: Relevance
“…Our results are in agreement with previous reports which indicated that the shifting of the peak is determined by crystal size, reaction temperature, solvent used, mode of synthesis, and the maturation time of samples. 41 43 …”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with previous reports which indicated that the shifting of the peak is determined by crystal size, reaction temperature, solvent used, mode of synthesis, and the maturation time of samples. 41 43 …”
Section: Resultsmentioning
confidence: 99%
“…Fine scan Zn 2p peaks exhibited major binary peaks detected at binding energy value of 1044.5 eV and 1021.5 eV consistent with Zn 2p1/2 and Zn 2p3/2 respectively which indicated the divalent oxidation state of ZnO. Further, energy separation between these two peaks is 23.0 eV which confirms the existence of Zn 2+ state in the ZnO crystal plane in nanofibers 41. Whereas, ZnO-GNI HNFs exhibited chemical shift to lower binding energy of 1020.4 and 1043.4 eV, associated to pure ZnO nanofibers due to accommodation of Au nanoislands over the surface of ZnO and existence of Zni defects in the nanograined structure.…”
mentioning
confidence: 55%
“…105,106,109,110 This kind of study is very promising and interesting because such LDH-nanohybrids could be developed into inorganicinorganic molecular structures for bio-imaging purposes. For example, various inorganic-inorganic nanohybrids, such as Au/ ZnO, 111 ZnO/Mn, 112 and CdTe/ZnTe nanohybrids, 51 were developed in order to improve photo-stability and thereby imaging capability in vitro and in vivo.…”
Section: Inorganic-inorganic Nanohybrids As Optical Imaging Agentsmentioning
confidence: 99%